2017
DOI: 10.1016/j.ejmech.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and in vivo study of novel pyrrolidine-based 11β-HSD1 inhibitors for age-related cognitive dysfunction

Abstract: Recent findings suggest that treatment with 11β-HSD1 inhibitors provides a novel approach to deal with age-related cognitive dysfunctions, including Alzheimer's disease. In this work we report potent 11β-HSD1 inhibitors featuring unexplored pyrrolidine-based polycyclic substituents. A selected candidate administered to 12-month-old SAMP8 mice for four weeks prevented memory deficits and displayed a neuroprotective action. This is the first time that 11β-HSD1 inhibitors have been studied in this broadly-used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Subsequently, we performed an in vivo study with 3 in the Senescence-Accelerated Mouse Prone 8 (SAMP8) model of cognitive dysfunction in order to support the neuroprotective effect of 11β-HSD1 inhibition in cognitive decline related to the aging process. We found that 3 , administered to 12-month-old SAMP8 mice for four weeks, prevented memory deficits and displayed a neuroprotective action through reduction of neuroinflammation and oxidative stress, in cognitive decline related to the aging process [ 17 ]. These promising results with an early lead without optimal selectivity and DMPK (drug metabolism and pharmacokinetics) properties led us to investigate additional potent 11β-HSD1 inhibitors that maintained the optimized polycycle of compound 2 while modifying the right-hand side (RHS) substituent of the structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, we performed an in vivo study with 3 in the Senescence-Accelerated Mouse Prone 8 (SAMP8) model of cognitive dysfunction in order to support the neuroprotective effect of 11β-HSD1 inhibition in cognitive decline related to the aging process. We found that 3 , administered to 12-month-old SAMP8 mice for four weeks, prevented memory deficits and displayed a neuroprotective action through reduction of neuroinflammation and oxidative stress, in cognitive decline related to the aging process [ 17 ]. These promising results with an early lead without optimal selectivity and DMPK (drug metabolism and pharmacokinetics) properties led us to investigate additional potent 11β-HSD1 inhibitors that maintained the optimized polycycle of compound 2 while modifying the right-hand side (RHS) substituent of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…A series of different substituents were integrated into the RHS moiety, while the amido linker was retained to enable the key hydrogen bonds in the binding site [ 17 ]. A diversity of substituents was generated including aromatic, heteroaromatic (electron-rich and deficient rings), branched alkyl, cycloalkenyl, heterocycloalkyl- and other groups inspired in previously reported 11β-HSD1 inhibitors from Abbott (a series of dichoroaniline amides [ 18 ], and ABT-384, which contains a 4-(pyridin-2-yl)piperazin-1-yl ring system) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the bicyclo[2.2.2]octane amide derivatives t well into the hydrophobic pocket of 11b-HSD1. 8 In this regard, propellanes containing bicyclo[2.2.2]octene derivatives with enhanced hydrophobicity are worthy targets of investigation for human 11b-HSD1.…”
Section: 6cmentioning
confidence: 99%
“…1). 8 The introduction of lipophilic substituents has proven to be a successful strategy to enhance the inhibition of 11b-HSD1 activity. IC 50 values of compounds 4-8 against 11b-HSD1 activity range from 0.02 to 0.03 mM.…”
Section: 6cmentioning
confidence: 99%